Identification of the 23-kDa peptide derived from the precursor of Gly m Bd 28K, a major soybean allergen, as a new allergen - Hiemori, Miki; Ito, Hitomi; Kimoto, Masumi; Yamashita, Hiromi; Nishizawa, Keito; Maruyama, Nobuyuki; Utsumi, Shigeru; Tsuji, Hideaki (Biochimica et biophysica acta, 2004)
One of the major soybean allergens, Gly m Bd 28K, is suggested to be biosynthesized as a preproprotein form, which would be composed of a signal peptide, Gly m Bd 28K and the C-terminal peptide (the 23-kDa peptide). However, the 23-kDa peptide has never been characterized. In the present study, we prepared a monoclonal antibody (mAb) against a recombinant 23-kDa peptide expressed in Escherichia coli to detect the 23-kDa peptide in soybean. Several proteins were detected by immunoblotting with the mAb. All of the proteins were shown to have the identical N-terminal amino acid sequence, suggesting that the proteins correspond to the C-terminal part of the Gly m Bd 28K precursor. Furthermore, Gly m Bd 28K and the 23-kDa peptide were observed to come out at the 21st day after flowering and to locate in the crystalloid part of protein storage vacuoles in growing cotyledons. Some of the 23-kDa peptides were shown to be glycoproteins with an N-linked glycan moiety and exhibited the binding to IgE antibodies in the sera of patients sensitive to soybean. The binding of the peptides to IgE antibodies was suggested to be predominantly dependent on their glycan moiety. This study proves the occurrence of the 23-kDa peptide in soybean and that it is a new allergen.